INTERNATIONAL INVESTMENT LAW IN CENTRAL ASIA - Sayokhat Akhrorova (Scholar Express Journal, 2022)
Despite the fact that Central Asian states have not been involved in regional invest-ment treaty-making on a scale and thrust similar to that of ASEAN and NAFTA, their evolving approaches to international investment law merit attention, not least because of the unique geopolitical characteristics of the region. The aim of this article is to fill the gap in the existing scholarship by exploring regional characteristics of Central Asian participation in international investment law-making. It will critically evaluate the history of numerous regionalisation efforts and, through a case study of two Central Asian states, Kazakhstan and Uzbekistan, examine the shared patterns in the evolution of national approaches to investment protection rules. In particular, the identity of Central Asian states as rule-takers and the factors underlying the emergence of distinctive national stances on the scope and objective of investment rules will be analysed.
Keywords: Investment; Eurasian regional cooperation; arbitration; national implementation